2005
DOI: 10.1128/jb.187.23.8172-8180.2005
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization ofYersinia pestisVirulence

Abstract: The Yersinia pestis proteome was studied as a function of temperature and calcium by two-dimensional differential gel electrophoresis. Over 4,100 individual protein spots were detected, of which hundreds were differentially expressed. A total of 43 differentially expressed protein spots, representing 24 unique proteins, were identified by mass spectrometry. Differences in expression were observed for several virulence-associated factors, including catalase-peroxidase (KatY), murine toxin (Ymt), plasminogen act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 83 publications
(72 reference statements)
4
71
0
Order By: Relevance
“…Outer membrane protein A (OmpA), also identified in our analysis, is known to be present in such vesicles and released by Gram-negative bacteria (11,30). OmpA has been detected in monocyte cell lysates after infection with Y. pestis (27), is known to bind scavenger receptors (31), and is considered a potent Yersinia virulence factor (30). Sif15, also known as systemic factor protein-a (Sfpa), is involved in systemic infection of Y. enterocolitica, is induced at 37°C, and is necessary for colonization of mesenteric lymph nodes in a mouse Peyer's patch infection model (32).…”
Section: Detection Of Injected Proteins In Host Cells By Fluorescencementioning
confidence: 93%
See 1 more Smart Citation
“…Outer membrane protein A (OmpA), also identified in our analysis, is known to be present in such vesicles and released by Gram-negative bacteria (11,30). OmpA has been detected in monocyte cell lysates after infection with Y. pestis (27), is known to bind scavenger receptors (31), and is considered a potent Yersinia virulence factor (30). Sif15, also known as systemic factor protein-a (Sfpa), is involved in systemic infection of Y. enterocolitica, is induced at 37°C, and is necessary for colonization of mesenteric lymph nodes in a mouse Peyer's patch infection model (32).…”
Section: Detection Of Injected Proteins In Host Cells By Fluorescencementioning
confidence: 93%
“…It seems likely that these highly abundant proteins are found in the HeLa cell lysate as a result of a low level of adventitious bacterial cell lysis, although we cannot rule out other mechanisms of transfer. Previous proteomic studies of factors secreted by Yersinia found subsets of these proteins, including HtpG, OmpA, GroL, and several elongation factors (27), as well as DnaK and Eno (28).…”
Section: Detection Of Injected Proteins In Host Cells By Fluorescencementioning
confidence: 99%
“…Although no data for the P. aeruginosa HSI-2 locus within the host are available, the HSI-3 gene cluster is upregulated in the presence of epithelial cell extracts (32). In Yersinia pestis, the YPO0499 gene cluster is induced at low temperatures and repressed at 37°C, suggesting that the role of the T6SS gene cluster is probably more important for dissemination in the flea vector than in human cells (29,31,47,49,73,85,93).…”
Section: Type VI Secretion Gene Clusters and The Hostmentioning
confidence: 99%
“…To evaluate whether the levels of Pla remained unaltered in the ⌬ail mutants, Western blot analysis was performed. Essentially, similar levels of the Pla protein were noted for the various mutant strains tested (⌬ail single, ⌬lpp ⌬msbB double, ⌬lpp ⌬msbB ⌬ail triple, as well as ail-complemented mutant strains) compared to that of WT CO92 at 37°C, a temperature that increases Pla production and activity (36,68,69) (Fig. 2D).…”
Section: Resultsmentioning
confidence: 69%